3D bioprinting of dECM-incorporated hepatocyte spheroid for simultaneous promotion of cell-cell and -ECM interactions - Kim, Min Kyeong; Jeong, Wonwoo; Jeon, Seunggyu; Kang, Hyun-Wook (Frontiers in Bioengineering and Biotechnology, 2023)
The cell spheroid technology, which greatly enhances cell-cell interactions, has gained significant attention in the development of in vitro liver models. However, existing cell spheroid technologies still have limitations in improving hepatocyte-extracellular matrix (ECM) interaction, which have a significant impact on hepatic function. In this study, we have developed a novel bioprinting technology for decellularized ECM (dECM)-incorporated hepatocyte spheroids that could enhance both cell-cell and -ECM interactions simultaneously. To provide a biomimetic environment, a porcine liver dECM-based cell bio-ink was developed, and a spheroid printing process using this bio-ink was established. As a result, we precisely printed the dECM-incorporated hepatocyte spheroids with a diameter of approximately 160–220 μm using primary mouse hepatocyte (PMHs). The dECM materials were uniformly distributed within the bio-printed spheroids, and even after more than 2 weeks of culture, the spheroids maintained their spherical shape and high viability. The incorporation of dECM also significantly improved the hepatic function of hepatocyte spheroids. Compared to hepatocyte-only spheroids, dECM-incorporated hepatocyte spheroids showed approximately 4.3- and 2.5-fold increased levels of albumin and urea secretion, respectively, and a 2.0-fold increase in CYP enzyme activity. These characteristics were also reflected in the hepatic gene expression levels of ALB, HNF4A, CPS1, and others. Furthermore, the dECM-incorporated hepatocyte spheroids exhibited up to a 1.8-fold enhanced drug responsiveness to representative hepatotoxic drugs such as acetaminophen, celecoxib, and amiodarone. Based on these results, it can be concluded that the dECM-incorporated spheroid printing technology has great potential for the development of highly functional in vitro liver tissue models for drug toxicity assessment.